The rove beetles (Coleoptera Staphylinidae) of three horticultural farms in Lombardy (Northern Italy) (Bollettino di zoologia agraria e bachicoltura, 2024)
Rove beetles (Staphylinidae) were surveyed across three horticultural farms, inserted in a peri-urban contest, in the Po plain in Lombardy (Northern Italy) from April 2003 to March 2005. Their biodiversity was estimated using pitfall traps. A total of 1341 specimens, 45 genera and 76 species were collected during the survey. Most of the species detected have already been recorded as frequent in other European agricultural fields. The rove beetle assemblage displayed the dominance of Drusilla canaliculata (Fabricius, 1787), Atheta aeneicollis (Sharp, 1869), Atheta triangulum (Kraatz, 1856) and Omalium caesum Gravenhorst, 1806, contributing to over half of the total number of the specimens detected. Land use seemed to have a significant effect on the number and composition of the species.
Keywords: bioindicators; rove beetles; agricultural crops; pitfall traps; land management